2020
DOI: 10.1002/dac.4292
|View full text |Cite
|
Sign up to set email alerts
|

Generalized frequency division multiplexing–based acoustic communication for underwater systems

Abstract: The underwater (UW) acoustic channel poses multiple challenges like coloured ambient noise, frequency-dependent attenuation, and doubly selective fading. The availability of a robust underwater communication mechanism can largely enhance the success of human effort in a multitude of applications, ranging from pollution surveillance to defence and search/ rescue operations. In this work, generalized frequency division multiplexing (GFDM), a non-orthogonal multicarrier scheme, which has recently been studied for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…It can be modelled as colored Gaussian noise and added to the transmitted signal. As evident, the noise is location specific and it is observed that the noise amplitude is high at both lower and higher frequencies whereas it is at its minimum around 60 kHz [21].…”
Section: (29)mentioning
confidence: 90%
See 1 more Smart Citation
“…It can be modelled as colored Gaussian noise and added to the transmitted signal. As evident, the noise is location specific and it is observed that the noise amplitude is high at both lower and higher frequencies whereas it is at its minimum around 60 kHz [21].…”
Section: (29)mentioning
confidence: 90%
“…Hebbar and Poddar (H&P) in [21] and [22] have analyzed a GFDM transceiver using statistical underwater acoustic channel model based on Rayleigh multipath fading. GFDM's low OOB leakages compared to CP-OFDM and the latter's ICI issue arising due to time variation/doppler spread, motivated H&P to explore GFDM for a doubly selective UWA channel.…”
Section: ) Gfdm Scheme For Uwa Communicationmentioning
confidence: 99%
“…It is observed that turbo codes outperform all other coding schemes investigated. Hebbar and Poddar [ 23 , 24 ] have proposed a GFDM modulated underwater acoustic transmission system. They used the Rayleigh distribution based multipath channel model along with ambient noise.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The noise is location specific and can be modeled as color noise, and its amplitude is high at both the lower and upper end of the spectrum while minimum around 60 kHz [58].…”
Section: Ambient Noisementioning
confidence: 99%